Long Non-Coding RNA LINC01572 Promotes Hepatocellular Carcinoma Progression via Sponging miR-195-5p to Enhance PFKFB4-Mediated Glycolysis and PI3K/AKT Activation - Lai, Shihui; Quan, Zhipeng; Hao, Yuesong; Liu, Jun; Wang, Zhiqian; Dai, Luo; Dai, Hongliang; He, Songqing; Tang, Bo (Frontiers in Cell and Developmental Biology, 2021)
Background: Accumulating evidence indicates Type 2 diabetes mellitus (T2DM) is a risk factor for hepatocellular carcinoma (HCC), and T2DM associated HCC represent a common type of HCC cases. We herein identify a lncRNA LINC01572 that was aberrantly upregulated in T2DM related HCC via high throughput screening. Based on this, this study was undertaken to identify the functional role and mechanism of LINC01572 in HCC progression. Methods: RT-qPCR was used to detect the expressions of LINC01572 in HCC tissues and cell lines. Gain- or loss-of function assays were applied to evaluate the in vitro and in vivo functional significance of LINC01572 in HCC cell proliferation, migration, and invasion using corresponding experiments. Bioinformatics, RIP, RNA Pull-down, and luciferase reporter assay were performed to explore the regulatory relationship of LINC01572/miR-195-5p/PFKFB4 signaling axis. Result: In this study, we profiled lncRNAs in HCC tissues and corresponding adjacent tissues from HCC patients with T2DM by RNA sequencing. Our data showed that LINC01572 was aberrantly upregulated in HCC tissues as compared with control, especially in those with concurrent T2DM. High level of LINC01572 was correlated with advanced T stage, increased blood HbA1c level, and shortened survival time. Overexpression of LINC01572 significantly promoted HCC cell proliferation, migration, invasion, and epithelial-to-mesenchymal transition (EMT), while knockdown of LINC01572 had the opposite effects on HCC cells. Mechanistic study revealed that LINC01572 regulated HCC progression via sponging miR-195-5p to increase the level of PFKFB4, and subsequent enhancement of glycolysis and activation of PI3K-AKT signaling. Conclusions: LINC01572 acts as a ceRNA of miR-195-5p to restrict its inhibition of PFKFB4, thereby enhances glycolysis and activates PI3K/AKT signaling to trigger HCC malignancy.